The Relevance of Gita for Business Management Sector (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
Management skill is an academic discipline. In this modern world the art of Management has  become a part and parcel of everyday life. It has gained application in other areas; governances,  political leadership development issues and even ethics. The Holy Bhagavod Gita is essence of  the Vedas and Upanisads. Gita is a universal scripture applicable to people of all temperaments  and for all times. Bhagavad Gita is one of the most popular and accessible of all Indian scriptures,  which is to be studied by anyone interested in Indian philosophy. Management principles come  into play through the management of resources, finance and planning, priorities, policies and  practice. The Gita teaches us that how one's aim in life can be achieved; howsoever it may be  difficult, by doing his duty with devotion, and meditation, integrating many different threads of  Indian philosophy. It gives correct solution to all the problems in human life. Bhagavad Gita  contains the essential ideas and basic principles of business management. Five priority areas  described in the Gita we must concentrate for better business management sector. These are  followings; ethics, energy, efficiency, effectiveness and excellence. If we do follow this properly,  we will win.  This paper aims at introducing the holistic vision of management sector enunciated in the Gita  which is more comprehensive than the 'Holistic View' of the modern management sector's theories  and practice. The concept of Gita used in modern management field and also try to looks at how  the Bhagavad Gita plays the important and significant role in the organisation to accomplish  various modern business management practices.
Keywords: Bhagavad Gita; Business Management; Leadership; Policy and Decision making